Державне регулювання та нагляд на фондовому ринку України - Зуєнко, Данило Петрович; Zuyenko, Danylo Petrovych (Ірпінь, 2024)
Проаналізовано фондовий ринок: сутність, функції та роль в економіці. Досліджено принципи та механізм державного регулювання фондового ринку. Здійснено оцінку сучасного стану розвитку фондового ринку України. Проаналізовано форми та методи державного регулювання та нагляду на вітчизняному фондовому ринку. Вивчено напрями підвищення ефективності державного регулювання на фондовому ринку України.

The stock market was analyzed: essence, functions and role in economy The principles and mechanism of state regulation of the stock market are studied. An assessment of the current state of development of the stock market of Ukraine was made. Forms and methods of state regulation and supervision on the domestic stock market are analyzed. The areas of increasing the effectiveness of state regulation on the stock market of Ukraine have been studied.
State regulation and supervision of the stock market of Ukraine
Keywords: фондовий ринок; фінансовий ринок; державне регулювання; нагляд; інвестиції; фінансова стабільність; stock market; financial market; government regulation; supervision; investment; financial stability